ABOUT PEDAGOGICAL CONDITIONS OF PROFESSIONAL ACTIVITY IN INCLUSIVE EDUCATION - Fazylova, А.А.; Allambergenova, K.Т. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
Professional training is a system of organizational conditions that ensures the development of the content of the main professional educational program of the relevant direction and profile of training, in order to form a student's professional orientation, general cultural, general professional and professional competencies.
Keywords: pedagogical conditions; inclusive education; professional training; tasks; conditions for the implementation of inclusive education word; word